Dukungan Habib Idrus bin Hasyim Alatas untuk Memenangkan Pasangan Anies-Sandi pada Pilkada DKI Jakarta - Fajar, Rachmad Al; Kamarudin, Kamarudin (Journal of Politics and Democracy, 2021)
Regional Head Elections (Pilkada) are a key form of local-level democracy. The 2017 Jakarta Special Capital Region (DKI) Pilkada showed that the incumbent was unable to retain power. This outcome was driven by multiple factors, including the involvement of Habib Idrus bin Hayim Alatas in the 2017 DKI Jakarta Pilkada, in which he participated as a representative of the Muslim community and Betawi culture. This study employs a qualitative case-study approach, with data collection procedures comprising interviews, observation, and documentation, and data-analysis techniques including data reduction, data display, and conclusion drawing. The findings indicate that Habib Idrus bin Hasyim Alatas supported the Anies–Sandi ticket by leveraging his social and cultural capital. He functioned as a source of religious legitimation, a facilitator, an opinion leader, and a mass mobilizer.